The History of the Iconostases of Vysokopetrovsky Monastery Churches According to the Written Sources of the Last Third of the 17th Century - Nikolaeva, Mariia V. (Actual Problems of Theory and History of Art, 2017)
The 1680–1690s witnessed the new construction stage of the Moscow Monastery of Sts. Peter andPaul on Petrovka street: the stone cathedral was put up in honour of the icon of Our Lady of Bogoliubsk, the St. Sergius of Radonezh church and the gate Pokrovskaya (Intercession) church were constructed; the renovationof St. Peter the Metropolitan cathedral of the beginning of the 16th century was accomplished. These events were accompanied by substantial modifications of the interiors of the monastery churches, in particular — new chancel screens were created or renovated. Unfortunately, today these monuments of applied art and icon paintingare almost completely lost, but still there is a foundation for their research: the contemporaries paid special attention to the monastery.The patronage of tsars Alexei Mikhailovich and Peter Alexeevich in the 17th century led to the production of iconostasis works by the best masters of the Armoury — woodcarvers, gongfermors, painters; an additional reason to turn to the history of the iconography of the churches of Visoko-Petrovsky Monastery in the 17th century was a range of unique archival documents which were gathered in the Russian State Archive of Ancient Acts, and that allowed us to reveal in detail the process of the creation of chancel screens, to reconstruct with varying degrees of detailization the appearance of four of them, to demonstrate the structure and the position of icons.The collected set of documents allowed us to determine the range of carpenters and carvers that worked on the hexastichous iconostasis with the crucifixion as well as on the ancient Peter the metropolitan cathedral including the talented master of carving of that time, Larion Yuriev; to identify the best icon painters (including Tikhon Filatiev, Georgii Zinoviev, Kirill Ulanov) and artists (i.e. Erofei Elena, Mikhail Choglokov and others) of the Armoury who painted the icons in the cathedral; to describe the fate of the dismantled iconostasis. The organization scheme, which was used for the construction of a wooden base of the stone Bogolyubsky cathedral, i.e., through subcontracting the leading carver of the Armoury Klim Mikhailov was involved; technological nuances applied in gilding of the frame and the decor of the iconostasis are seen in the work descriptions of master Dorofei Zolotarev, who in those years was involved in major projects of the Armoury; iconpainting work led by the famous master of icon painting, Fyodor Zubov — which is remarkable, due to the fact that the high iconostasis of Bogolyubsky cathedral appears in the documents not only in its entirety, but also with a list of names of masters who created its iconic images.The thorough analysis of the written sources of the 17th century allows us to reveal objects that are physically lost and to include them into art history for further study.